Efficient one pot regioselective synthesis of a 3,3 `-spiro-phosphonylpyrazole-oxindole framework via base mediated [1,3]-dipolar cycloaddition reaction of the Bestmann-Ohira reagent with methyleneindolinones - Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2015)
A one pot, highly regioselective synthesis of racemic 3,3'-spiro-phosphonylpyrazole-oxindole by 1,3-dipolar cycloaddition of an in situ generated anion of dialkyl 1-diazomethylphosphonate from the Bestmann-Ohira reagent (BOR) & methyleneindolinones has been developed. The synthesis affords the highly functionalized pyrazole scaffolds in good yields with excellent regioselectivity under mild reaction conditions within a short reaction time.